Composition and Culture of Eating (CoCu) pregnancy: a new short questionnaire to evaluate diet composition and culture of eating during pregnancy. Issue 18 (28th December 2021) - Spielau, Ulrike; Vogel, Mandy; Körner, Antje; Kiess, Wieland; Poulain, Tanja
Abstract: Objective: The project aimed to validate a short questionnaire (CoCu pregnancy – Composition and Culture of Eating during pregnancy) and to investigate associations with age and socio-economic status (SES). Design: The questionnaire was developed according to the validated CoCu for children and adolescents containing a diet composition (fourteen items) and a culture of eating part (six items). A Nutritional Health Score (NHS) was calculated based on diet composition (–120 and +120, with higher scores indicating healthier diets). The validity was assessed by comparing answers in CoCu pregnancy with a FFQ. In a subsample ( n 97), we assessed the percentage of having chosen the same (or adjacent) response categories in the 24th and 36th week of pregnancy (wp). Setting: Data were collected within the LIFE Child study in Leipzig, Germany. Participants: We evaluated 430 questionnaires of pregnant women (24th wp). Results: The results indicated a healthy diet in the present sample (NHS at 24th wp = 49·74 (95 % CI 47·27, 52·22)). The analyses revealed significant positive correlations between CoCu and FFQ (rho ranging from 0·32 to 0·61). For each food item, >90 % of women had chosen the same (50–60 %) or adjacent response categories in the 24th and 36th wp. The analysis revealed associations of the NHS with age ( β = 0·11, P = 0·027), SES ( β = 0·21, P < 0·001), snacking (β = –0·24, P < 0·001) and media use ( β = –0·18, P < 0·001). Conclusions: The questionnaire represents a useful tool for surveying the diets during pregnancy for research and clinical practice.